Diagnóstico da situação dos resíduos de construção e demolição (RCD) no município de Petrolina - Santos, Almai do Nascimento dos (2008)
Besides the fact that it is the cause of some environmental impact due to the great consumption of raw material and generation of residues, construction engineering is recognized as one amongst the most important activities that contributes to the economic and social development of our country. Within underdevelopment countries the generation of CDW (Construction and Demolition waste) in demolition works between the years 94-99 varied from 32 to 99 tons/year. CDW in Brazil is not different. In 2005, a research carried in 11 municipalities showed that the medium CDW was 59% as well. The municipality of Petrolina is located in the arid backlands of the state Pernambuco, the current population is 268,339 and still doesn t own a system for management of the CDW as required in the resolution 307 of CONAMA(2002) (National Council for Environmental Issues). Willing to contribute to the solving of this problem, the present dissertation brings a survey of variability of CDW in the municipality of Petrolina and verifies its recycling potential. The research is based on exploratory and descriptive field work and aims to identify the varied waste material discarded through the work of ten civil engineering companies and also to identify 11(eleven) points of irregular discard and the possible re-use of the discarded material. Results show that 91, 2% of residues are class A, waste with recycling potential. 45, 5% of the waste is ceramic, 23, 6% is mortar, 14, 1% is concrete and 8% is sand. The other 8, 8% are discard of wood, plastic and plaster. Despite the lack of place for disposal, private and governmental companies try to adjust themselves to what is required in resolution 307, specially regarding to recycling of CDW.There have been implemented a recycling industry in a disposal area called Raso da Catarina therefore providing jobs for the population. The present work of study also suggests some future action that may collaborate in studies for the use of CDW aggregates for paving, blocks with non-structural function and pieces for sidewalk, benefitting population and municipality as a whole